2001
DOI: 10.1007/s002940100233
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous loss of a conditionally dispensable chromosome from the Alternaria alternata apple pathotype leads to loss of toxin production and pathogenicity

Abstract: The Alternaria alternata apple pathotype causes Alternaria blotch of susceptible apple cultivars through the production of a cyclic peptide, host-specific toxin, AM-toxin. We recently cloned a cyclic peptide synthetase gene, AMT, whose product catalyzes the production of AM-toxin and showed that it resides on chromosomes of 1.8 Mb or less, depending on the A. alternata apple pathotype strain. Reverse transcriptase (RT)-PCR, using primers specific to AMT, on laboratory sub-cultured strains previously shown to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 0 publications
1
84
0
4
Order By: Relevance
“…Host-selective toxin biosynthetic genes of A. alternata pathotypes appeared to be clustered on small chromosomes of Ͻ2.0 Mb in most of the strains tested (2,3,13,15,20,21,33,35). We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Host-selective toxin biosynthetic genes of A. alternata pathotypes appeared to be clustered on small chromosomes of Ͻ2.0 Mb in most of the strains tested (2,3,13,15,20,21,33,35). We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21).…”
Section: Discussionmentioning
confidence: 95%
“…We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21). We are now focusing on the structural and functional analysis of the 1.05-Mb CD chromosome that contains the AFT genes of the strawberry pathotype to identify the entire gene cluster and to understand the evolution of toxin biosynthesis and the origin of CD chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In Alternaria alternata plant pathogens (37), we have shown that all strains of the A. alternata pathotypes harbor small extra chromosomes of less than 1.7 Mb, whereas nonpathogenic isolates do not have these small chromosomes (5). A cyclic peptide synthetase gene, AMT, which is involved in host-specific AM toxin biosynthesis of the apple pathotype of A. alternata, was located on a small chromosome of 1.1 to 1.7 Mb, depending on the strain (22,23). The AF toxin biosynthesis gene cluster was also present on a single small chromosome of 1.05 Mb in the strawberry pathotype of A. alternata (18).…”
mentioning
confidence: 99%
“…The AF toxin biosynthesis gene cluster was also present on a single small chromosome of 1.05 Mb in the strawberry pathotype of A. alternata (18). Based on biological and pathological observations, those small chromosomes were regarded as supernumerary chromosomes, or conditionally dispensable chromosomes (CDCs) (10,18,22). Fungal supernumerary chromosomes, which are not important for normal growth but confer advantages for colonizing an ecological niche, such as infecting host plants, are regarded as CDCs (21).…”
mentioning
confidence: 99%
“…These chromosomes are known to be easily lost from the www.intechopen.com genome, probably because they are unnecessary (Johnson et al, 2001). This property could be adaptatively advantageous because pathogen population can adapt quickly to cultivars carrying correspondent R genes by losing supernumerary chromosomes.…”
Section: Mutationmentioning
confidence: 99%